A Pretreatment Method for Analysis of Available Tetracycline in Soils. Issue 3 (3rd April 2022) - Shi, Yongning; Wang, Yixiang; Cao, Haiyan; Shan, Xinxin; Su, Yuhong
ABSTRACT: A pretreatment method for detecting the available (water-soluble) tetracycline (TC) contents in soils was developed using a molecularly imprinted polymer (MIP) synthesized with TC as the template. The infrared spectroscopy, scanning electron microscopy, and TC sorption isotherms revealed a specific TC binding with the synthesized MIP in water. Upon extraction and concentration from water by the MIP, the target TC could be directly analyzed by high-performance liquid chromatography (HPLC). The parameters for the pretreatment method were optimized with TC-spiked water and soils, with observed TC recoveries from water and soils equal to 74.7 ± 4.6% to 95.5 ± 6.5% (n = 3) and 48.1 ± 3.3% to 72.1 ± 2.7% (n = 3), respectively. The detected available TC contents in three test soil samples were in the range of 2.3 ± 0.1 to 3.0 ± 0.1 μg/kg (n = 3), only13.8%-39.4% of the TC contents detected by the conventional solvent-extraction method coupled with a solid-phase extraction (SPE) technique. The observed TC distribution in a vertical soil profile indicated that the proposed method for available antibiotic content coupled with the total extracted antibiotic content via the conventional (organic-solvent) extraction can be utilized to evaluate the available TC level and its mobility in contaminated soils.